CXCR2 intrinsically drives the maturation and function of neutrophils in mice - Delobel, Pauline; Ginter, Benjamin; Rubio, Eliane; Balabanian, Karl; Lazennec, Gwendal (Frontiers in Immunology, 2022)
Neutrophils play a major role in the protection from infections but also in inflammation related to tumor microenvironment. However, cell-extrinsic and -intrinsic cues driving their function at steady state is still fragmentary. Using Cxcr2 knock-out mice, we have evaluated the function of the chemokine receptor Cxcr2 in neutrophil physiology. We show here that Cxcr2 deficiency decreases the percentage of mature neutrophils in the spleen, but not in the bone marrow (BM). There is also an increase of aged CD62Llo CXCR4hi neutrophils in the spleen of KO animals. Spleen Cxcr2-/- neutrophils display a reduced phagocytic ability, whereas BM neutrophils show an enhanced phagocytic ability compared to WT neutrophils. Spleen Cxcr2-/- neutrophils show reduced reactive oxygen species production, F-actin and alpha-tubulin levels. Moreover, spleen Cxcr2-/- neutrophils display an altered signaling with reduced phosphorylation of ERK1/2 and p38 MAPK, impaired PI3K-AKT, NF-KB, TGFbeta and IFNgamma pathways. Altogether, these results suggest that Cxcr2 is essential for neutrophil physiology.